KEMAMPUAN LITERASI TEKNOLOGI SISWA KELAS X DALAM PEMBELAJARAN GEOGRAFI PADA MATERI DINAMIKA ATMOSFER DAN PENGARUHNYA BAGI KEHIDUPAN - Waty Sirait, Mawar; Afdhal (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Technological literacy has become an important competence in 21st century education. The rapid development of information and communication technology requires students to be able to utilize digital technology effectively in the learning process. This study aims to determine the level of technological literacy ability of tenth grade students in geography learning on atmospheric dynamics material and its influence on life at SMA Pembangunan Laboratorium UNP. This research employed a descriptive quantitative method. The population of this study was all tenth grade students totaling 146 students, while the sample consisted of 60 students selected using proportional random sampling technique. Data were collected using questionnaires based on Likert scale and analyzed using descriptive statistical techniques with percentage analysis. The results showed that students' technological literacy ability was in the sufficient category with an average percentage of 71%. The content indicator obtained 68%, the process indicator obtained 71%, the context indicator obtained 72%, and the attitude indicator obtained 74%. These findings indicate that students already have basic technological literacy skills, but their ability to critically evaluate digital information and optimally utilize technology for learning still needs improvement. Therefore, teachers need to integrate technology-based learning strategies to improve students’ technological literacy in geography learning.